Características clínicas e epidemiológicas da Pitiríase Versicolor em pacientes atendidos no Hospital Universitário Cassiano Antônio Moraes-Vitória (Espírito Santo-Brasil) e no Instituto Dermatológico Dr. Huberto Bogaert Diaz-Santiago de Los Caballeros-República Dominicana - Solis, Aniberka Del Carmen Rosario (2017)
Background: Pityriasis versicolor (PV) is a superficial chronic fungal infection produced by the yeast Malassezia spp. Pityriasis versicolor predominates in young adults, without significant differences between the sexes. Characterized by hyperpigmented or hypopigmented macules, round to oval, with furfuraceus scaly and mild pruritus, are most commonly found on seborrheic areas of the body. Diagnosis is made by the clinical presentation, Woods lamp and KOH examination. Objective: The aim of the present study was to describe and to compare the clinical presentation and the epidemiology in patients with PV in both populations. Methodology: Crosssectional study performed between November 1, 2015 and November 30, 2016. Patients with clinical diagnosis of PV were included. Statistic test X2 was performed and frequency of sociodemografic and clinical variables. Results: A total of 95 patients were included, 53 from HUCAM and 42 from IDCP. The most affected age group was between 21 and 30 years in both groups. As well females were most affected, in IDCPRep. Dom. 27 (64.3%) and 36 (67.9%) in HUCAM group, without significant difference between groups. The race in IDPC- Rep. Dom. patients was predominantly mixed -19 (45.2%)- and in HUCAM group were black 30 (56.6%). Hypopigmented macules were predominant in 30 (71.4%) patients from IDCP- Rep. Dom and in 34 (64.2%) in HUCAM group. In IDCP- Rep. Dom group 97.6% of the patients refer lesions appear in the last year, as well as 66% of HUCAM patients, with statical significance (p value<0.000). In other side, in both groups, the most affected body part was the trunk. Thirty one of IDCP- Rep. Dom patients (73.8%) confirms at least one relapsing episode of PV and 34 (64.2%) in HUCAM. Malassezia cultures were seeded, but not fungi colonies were evidenced, because of that was impossible to identify malassezia species. Conclusion: both groups show similar results, due to the geographic characteristics of both scenarios.